ANALISA PENERAPAN STRATEGI INTERNASIONAL PADA PERUSAHAAN NESTLE - Wirren Chang; Agnes Doraresta Khatarina Tokan; Delfina Muthia Sabella; Dewi Dewi; Mardiana Ng; Serina Serina (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Companies can continue to be sustainable or last a long time when the company has the right strategy in running its business. Nestlé is a company that has a good strategy in running and developing its business since 1866 which has made the Nestlé company survive to this day. This study discusses the strategies used by Nestlé, such as business-level strategies and international corporate strategies. The methodology used by researchers is the method of literature study. The Nestlé company uses a low cost strategy and also uses a joint venture business form. In addition, Nestle also acquired the company Pfizer Nutrition. Nestle's goal is to achieve a competitive advantage from products marketed in various market segments so that it can expand its target globally.